Erratum to: Framework for Patient Safety - AK Mohiuddin (University of Minnesota Libraries Publishing, 2020)
The original article https://pubs.lib.umn.edu/index.php/innovations/article/view/1637 was published on 2019-02-08 .This article has been retracted by the Editor and Publisher due to the inappropriate use of previously published work. This article has been retracted: please see INNOVATIONS in pharmacy retraction policy (https://pubs.lib.umn.edu/index.php/innovations/policies).